2018
DOI: 10.1177/1066480718795123
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness as a Moderator of Clinician History of Trauma on Compassion Satisfaction

Abstract: Compassion satisfaction is an understudied phenomenon in the counseling literature. The impact of a clinician's history of trauma on compassion satisfaction and potential protective factors that may enhance feelings of compassion satisfaction is equally understudied. This study aimed to address models of mindfulness as a protective factor for the associations between a clinician's history of trauma and their experience with compassion satisfaction. The sample consisted of licensed clinicians (N ¼ 113) reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 88 publications
(154 reference statements)
0
5
0
1
Order By: Relevance
“…Since then, the literature on shared resilience or growth specific to care providers experiencing collective stress alongside their communities has not expanded, to our knowledge. However, while Martin-Cuellar (Martin-Cuellar, 2017) found that aggregated past or recent trauma of a clinician did not have a relation to compassion fatigue, recent trauma was positively related to compassion satisfaction. This was proposed to be a result of clinician ability to process or reflect on their trauma in more current emotional states.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Since then, the literature on shared resilience or growth specific to care providers experiencing collective stress alongside their communities has not expanded, to our knowledge. However, while Martin-Cuellar (Martin-Cuellar, 2017) found that aggregated past or recent trauma of a clinician did not have a relation to compassion fatigue, recent trauma was positively related to compassion satisfaction. This was proposed to be a result of clinician ability to process or reflect on their trauma in more current emotional states.…”
Section: Resultsmentioning
confidence: 95%
“…Baum (Baum, 2014) wrote on unique characteristics of shared trauma, including lapses of empathy, immersion in the professional role, role expansion, and changes in the place and time of work. Narratives in the literature have mostly emphasized this blurring of therapeutic boundaries in the provider–patient relationship and personal spheres (Boulanger, 2013; Rao & Mehra, 2015; Tosone et al, 2003); the issue of self-disclosure (Bown, 2015); and the countertransference of clinicians as both necessary tool and hindrance to the therapeutic process (Martin-Cuellar, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the importance of a supportive work environment that allows workers space to process the complexity of the cases they deal with. Despite the positive relationship between client trauma experience and compassion satisfaction (Craig & Sprang, 2010; Figley, 1995), participants still signaled a crucial need to have the space to disburden themselves to routinely process trauma in a safe way, showing a lack of immunity to trauma regardless of training and experience (Bent-Goodley, 2018; Martin-Cuellar et al, 2018). Participant 8 shared,I don’t think I would be working ethically or safely if I didn’t have some other accountability or another way in which I can kind of verbally work through what’s going on erm, with my clients to get support in dealing with individual cases but also in managing my own, making sure I’m cared for.…”
Section: Methodsmentioning
confidence: 99%
“…Birçok araştırmada, merhamet doyumu ile merhamet yorgunluğunun birlikte incelenmiş (DePanfilis, 2006; Annalakshmi ve Jayanthy, 2019) ve merhamet doyumu ile merhamet yorgunluğu arasında negatif ve anlamlı bir korelasyon bulunduğu belirtilmiştir (Kim, Ha ve Jue, 2020;Jarrad ve Hammad, 2020). Ayrıca yapılan araştırmalarda merhamet doyumunun öz bakım (Alkema ve diğerleri, 2008), farkındalık (Decker, Brown, Ong ve Stiney-Ziskind, 2015;Martin-Cuellar, Atencio, Kelly ve Lardier, 2018), öz bakım aktiviteleri, değerlerin gelişmesi (Stainfield ve Baptist, 2019), duygusal uyumsuzluk (Kim, Ha ve Jue, 2020), tükenmişlik (Jarrad ve Hammad, 2020), olumlu duygular/düşünceler, stres yönetimi, zihinsel, sosyal ve fiziksel kaynaklar (Radey ve Figley, 2007) gibi pek çok faktörle ilişkili olduğu saptanmıştır.…”
Section: Gġrġġunclassified